Botanical insecticides applied on Aphis gossypii and its predator Cycloneda sanguinea on naturally colored cotton - Breda, Mariana Oliveira; Oliveira, José Vargas de; Marques, Edmilson Jacinto; Ferreira, Rachel Gonçalves; Santana, Mauricéa Fidelis (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effects of botanical insecticides on Aphis gossypii and its predator Cycloneda sanguinea, in naturally colored cotton. The botanical insecticides based on azadirachtin, aqueous extract of nim seeds, and castor oil were tested at the concentrations from 0 to 2%, 0 to 2.5%, and 0 to 3%, respectively. The bioassays were performed in laboratory conditions, in a completely randomized design. Aphid mortality ranged from: 64 to 100% for azadirachtin; 12 to 92% for nim aqueous extract; and 8 to 68% for castor oil. The instantaneous rate of increase reached negative values starting from concentrations of: 1.25%, for azadirachtin; 2.25%, for nim aqueous extract; and 3.0%, for castor oil emulsion. All insecticides were toxic to the first instar larvae of the predator, with mortality values from 96.7 to 100%, for azadirachtin and nim aqueous extract, and from 50 to 100% for castor oil emulsion. For the 4th instar larvae, mortalities ranged from 87.5 to 100% for azadirachtin; from 73.3 to 100% for nim aqueous extract; and from 43.3 to 100% for castor oil emulsion. The tested insecticides are promising for A. gossypii management, although they are not selective toward C. sanguinea.